Dynamic Governance of Public Services in Passport Making at the Class 1 Immigration Office For the City of Surabaya - Faqim Adinul Falah; Fedianty Augustinah; Sapto Pramono; Widyawati Widyawati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to describe and analyze: How is the Dynamic Capability of the Special Class I Immigration Office of Surabaya in Passport Making Services. The research method to be used is qualitative descriptive. Data Collection Techniques include: Interviews, Observations, Documentation. The research informant is the Head of the Suarabaya Special Class I Immigration Office. The data analysis technique using interactive model analysis was developed by Miles et al., (2014), namely data condensation, data presentation, and conclusion drawn. The results of the study show that the dynamic capability of the Surabaya Special Class I Immigration Office in the implementation of passport services is able to produce various positive changes in service, which has an impact on improving the quality of passport services better in the eyes of the public. However, there are still several aspects that need to be improved in the implementation of this dynamic capability, especially in exploring feedback from passport applicants in more depth as part of the thinking again mindset, as well as studying service practices from the private sector or foreign immigration to realize a thinking across mindset. The process of forming dynamic capabilities at the Surabaya Special Class I Immigration Office begins with the leadership role of the head of the immigration office who regularly holds meetings with employees. This encourages employees to create various innovations in service, which is a manifestation of the thinking ahead mindset. Service performance evaluation activities that are carried out regularly bring changes in service policies, as an implementation of the thinking again mindset. In addition, an open attitude to learn service practices from other parties through comparative studies with other immigration offices is also part of the application of a thinking attitude mindset.